2023
DOI: 10.7150/thno.79538
|View full text |Cite
|
Sign up to set email alerts
|

Repopulated retinal microglia promote Müller glia reprogramming and preserve visual function in retinal degenerative mice

Abstract: Rationale: Müller glia (MG) play a key role in maintaining homeostasis of the retinal microenvironment. In zebrafish, MG reprogram into retinal progenitors and repair the injured retina, while this MG regenerative capability is suppressed in mammals. It has been revealed that microglia in zebrafish contribute to MG reprogramming, whereas those in mammals are over-activated during retinal injury or degeneration, causing chronic inflammation, acceleration of photoreceptor apoptosis, and gliosis of MG.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…Thus, we investigated whether transplanted hAECs degrade inhibitory ECM components via secreting Mmp2 and Mmp9 to induce retinal regeneration. Consistent with our findings, ECM components, including CSPGs and collagen Ι, were deposited in the degenerative retina (Figure 5a-d) 42 . Almost no CSPGs were found in the retinas of C57 mice, whereas a clear CSPG band was deposited in the ONL and the external limiting membrane (ELM) (Figure 5a, b).…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Thus, we investigated whether transplanted hAECs degrade inhibitory ECM components via secreting Mmp2 and Mmp9 to induce retinal regeneration. Consistent with our findings, ECM components, including CSPGs and collagen Ι, were deposited in the degenerative retina (Figure 5a-d) 42 . Almost no CSPGs were found in the retinas of C57 mice, whereas a clear CSPG band was deposited in the ONL and the external limiting membrane (ELM) (Figure 5a, b).…”
Section: Resultssupporting
confidence: 91%
“…Excessive deposition of ECM components such as chondroitin sulfate proteoglycans (CSPGs) is frequently associated with CNS damage, including RD, which is a critical barrier to neuronal repair and regeneration 4245 . On the one hand, GO and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis of the top 200 genes in hAECs showed that pathways related to ECM regulation including regulation of cell-substrate adhesion, collagen metabolic process, regulation of peptidase activity and ECM-receptor interaction were enriched (Figure S9a, b) 46 ; on the other hand, hAECs with high Mmp2 and Mmp9 expression degrade ECM components during parturition 47 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations